2005
DOI: 10.1002/mds.20505
|View full text |Cite
|
Sign up to set email alerts
|

Speech‐activated myoclonus: An uncommon form of action myoclonus

Abstract: We describe an unusual form of facial myoclonus activated by speech in 3 patients with different underlying neurological diseases and present the electrophysiological investigations and results of structural and functional imaging. In 1 of 2 patients in whom jerk-locked electroencephalogram (EEG) back-averaging was done, a cortical potential clearly preceded the facial jerks. In the second patient, a cortical potential preceding the jerk was not certain. In the third patient, the resting EEG contained outburst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Speechactivated myoclonus is typically a function of the type of speech: spontaneous or rote. 5 In their case series, Slee et al 5 demonstrated that oropharyngeal movements not involving the vocal cords (e.g. whistling, chewing, swallowing) failed to trigger myoclonus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speechactivated myoclonus is typically a function of the type of speech: spontaneous or rote. 5 In their case series, Slee et al 5 demonstrated that oropharyngeal movements not involving the vocal cords (e.g. whistling, chewing, swallowing) failed to trigger myoclonus.…”
Section: Discussionmentioning
confidence: 99%
“…The neural substrate of acquired neurogenic stuttering remains elusive, in large part because of the myriad brain structures and varied etiologies implicated. 1,4 Speech-activated myoclonus is a rare entity that can mimic stuttering and, like stuttering and other forms of myoclonus, is caused by a wide array of etiologies, most of which are acquired: neurodegenerative disease, 5 clozapine, 5,6 pharyngitis, 5 reading epilepsy, 7 reflex seizures in the context of juvenile myoclonic epilepsy, 7,8 localization-related epilepsy secondary to hypoxic brain injury, 9 Lance-Adams syndrome, 10 and as an unclear consequence of primary intestinal T-cell non-Hodgkin's lymphoma. 11 Here we report a patient with genetic dystonia, myoclonus-dystonia syndrome (MDS), with an identified disease-causing mutation who presented with speech-activated myoclonus mimicking stuttering.…”
Section: Introductionmentioning
confidence: 99%
“…Speech-activated myoclonus is typically a function of the type of speech: spontaneous or rote. 5 In their case series, Slee et al 5 demonstrated that oropharyngeal movements not involving the vocal cords (e.g. whistling, chewing, swallowing) failed to trigger myoclonus.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also noted that “internal speech” and writing did not activate myoclonus, concluding that in all three patients, the myoclonus was elicited by vocal speech production. 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation